Determination of Fast Voltage Stability Index (FVSI) using Evolutionary Programming (EP) technique to maintain system stability / Norhafizah Zulkipli - Zulkipli, Norhafizah (2014)
Nowadays, electrical energy used is increasing from day onwards, so in order to meet the demand, power systems are operating closer to their maximum capacity which will cause higher risk to the power system instability. It also will cause the shutdown of entire power system. Thus, this paper proposes an application of Fast Voltage Stability Index (FVSI) to power system stability using Evolutionary Programming (EP) technique. FVSI is used to verify the stability of the systems based on the variation of reactive power load. The value of FVSI close to unity shows that the line has reached its instability limit. This could cause sudden voltage drop to the corresponding bus. EP technique involves mutation process which is used to generate offspring from parents. The biggest advantage of EP is it allows development of complex applications which in tum the solution will fit the needs of the users. The standard IEEE 30-bus test system has been used as a case study in this research. This paper shows the relationship between the numbers of reactive power load bus, search step size and number of population with total losses and value of FVSI. From the simulation results, it indicates that the proposed technique has been able to reduce the system losses and able to verified the voltage stability system with the application of FVSI.